2019
DOI: 10.1002/iub.2055
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin enhances autophagy and decreases apoptosis induced by nanosilica in RAW264.7 cells

Abstract: Melatonin is one of the main hormones that regulate biological rhythms and have immunomodulation, anti‐inflammatory, and antioxidation functions. In this study, we aimed to explore the effect of melatonin on the autophagy, apoptosis, and inflammatory reaction of macrophages (RAW264.7 cells) stimulated by nanosilica. SiO2 (100 mg/mL, 10–20 nm) was used to stimulate RAW264.7 cells at different time points (0, 2, 4, 8, 12, and 24 hr). Melatonin (200 μM) was added to SiO2‐stimulated macrophages at 12 hr. Beclin‐1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…Of the different compounds evaluated, the phenanthroimidazole 6 derivative was found to induce autophagy and apoptosis; thus, it could prove to be a novel anti-cancer drug [516]. In nanosilica stimulated RAW264.7 cells, melatonin was found to increase LC3 expression and decrease Bax expression, suggesting that autophagy was promoted, and apoptosis was inhibited [517]. Sasanquasaponin ΙΙΙ obtained from Schima crenata Korth was found to upregulate LC3-II expression in melanoma cells and induce autophagy; hence, it can be used as an anti-cancer drug to treat melanoma [518].…”
Section: Treatment Of Autophagy-associated Diseasesmentioning
confidence: 99%
“…Of the different compounds evaluated, the phenanthroimidazole 6 derivative was found to induce autophagy and apoptosis; thus, it could prove to be a novel anti-cancer drug [516]. In nanosilica stimulated RAW264.7 cells, melatonin was found to increase LC3 expression and decrease Bax expression, suggesting that autophagy was promoted, and apoptosis was inhibited [517]. Sasanquasaponin ΙΙΙ obtained from Schima crenata Korth was found to upregulate LC3-II expression in melanoma cells and induce autophagy; hence, it can be used as an anti-cancer drug to treat melanoma [518].…”
Section: Treatment Of Autophagy-associated Diseasesmentioning
confidence: 99%
“…The protective effect of melatonin, which can defend chromosome damage and oxidative stress induced by environmental toxins has been confirmed by experiments both in vitro and in vivo. In addition, some other studies also showed that melatonin could regulate the autophagy in the protection against oxidative stress 28,29 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, some other studies also showed that melatonin could regulate the autophagy in the protection against oxidative stress. 28,29 Autophagy is a process to degrade its own organelle and other macromolecules through lysosome, featured by the formation of autophagosome. 30 The stimulation of autophagy could maintain homeostasis and viability of normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, melatonin is produced in some reproductive tissues such as ovaries, uterus, placenta, and testes. Melatonin is considered a multitasking molecule that regulates many cellular functions, including: antioxidant and anti-apoptotic properties [ 27 29 ], induction of autophagy [ 30 , 31 ], regulation of epigenetic enzymes [ 5 , 22 ], and telomere length [ 22 , 32 ].…”
Section: Introductionmentioning
confidence: 99%